2021
DOI: 10.1096/fj.202101045rr
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading alleviated the inhibition of β2‐adrenergic receptor agonist terbutaline on bone regeneration

Abstract: The long-term use of adrenergic medication in treating various conditions, such as asthma, increases the chances of bone fracture. Dynamic mechanical loading at a specific time is a method for improving bone quality and promoting healing.Therefore, we hypothesized that precisely controlling the mechanical environment can contribute to the alleviation of the negative effects of chronic treatment with the common asthma drug terbutaline, which is a β2adrenergic receptor agonist that facilitates bone homeostasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…9 Previous studies have shown mechanical stimulation could increase Type H vessel volume, suggesting that Type H vessels respond to mechanical stimulation. 12,36 is a key regulator in vascularization and sprouting angiogenesis 26,37 and has been shown to be a mechanosensitive protein in vascular ECs. 27,28 However, whether and how S1Pr1 in Type H vessels regulates bone repair is not clear, especially after controlled mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Previous studies have shown mechanical stimulation could increase Type H vessel volume, suggesting that Type H vessels respond to mechanical stimulation. 12,36 is a key regulator in vascularization and sprouting angiogenesis 26,37 and has been shown to be a mechanosensitive protein in vascular ECs. 27,28 However, whether and how S1Pr1 in Type H vessels regulates bone repair is not clear, especially after controlled mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Type H vessels are unique to the bone, associated with bone modeling and remodeling, and defined by high expression of CD31 and Emcn 9 . Previous studies have shown mechanical stimulation could increase Type H vessel volume, suggesting that Type H vessels respond to mechanical stimulation 12,36 . S1Pr1 is a key regulator in vascularization and sprouting angiogenesis 26,37 and has been shown to be a mechanosensitive protein in vascular ECs 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical loading induces the innervation of sensory and sympathetic neurons inhabiting the skeletal system. Wang et al recently found that mechanical loading significantly reversed β2-AR agonist terbutaline-induced bone loss, 114 suggesting that sympathetic modulation of bone metabolism may be closely associated with the endocrine system or sensory nerve interoception relay. Given these promising findings, further investigation of this regulatory pathway is warranted.…”
Section: Central Processing Of Interoception To Coordinate Autonomic ...mentioning
confidence: 99%
“…βARs are subdivided into three groups: β1ARs, β2ARs, and β3ARs. Osteoblasts mainly express the β2AR subtype [ 84 , 94 , 95 ]. While β1ARs and β3ARs were found to be weakly expressed or even undetectable in osteoblasts and osteoclasts [ 96 ].…”
Section: Crosstalk Between Bone and Brainmentioning
confidence: 99%